INTERROGATING ENFEEBLING SYNDROME: CORRUPTION AND ABUSE OF PUBLIC OFFICE IN CHIMAMANDA ADICHIE’S TRILOGY - Ike, Onyeka (International Journal of Research -GRANTHAALAYAH, 2023)
The sickening and enervating stench named corruption is a global malady which robs many nations of their endowed fortune. In a developing country like Nigeria, the situation is exacerbated by the absence of strong institutions as opposed to the palpable and pervasive cults of strong personalities. The aftermath of the unwholesome scenario is that poverty takes the seat of prosperity while pieces assume the place of peace. Indeed, corruption and commodification of public office are twin cankerworms actively devouring the supposed brilliant destinies and destinations of nations as amply foregrounded and demonstrated in Chimamanda Adichie’s Purple Hibiscus (2003), Half of a Yellow Sun (2006), and Americana (2013). Utilizing Michel Foucault’s New Historicist theory of power and qualitative research methodology, the study uncovers that although Adichie’s home country, Nigeria, is beautifully endowed with unequivocal elements of greatness, it is yet to attain such a noble status principally on account of corruption and abuse of public office as brazenly perpetrated from inception by the operators of its political, administrative, and bureaucratic machineries. The study avers that for the nation to realise and maximise its baronial endowments, the putrefaction of corruption and commodification of public office must be firmly dealt with, and that the evolution of formidable and dependable institutional frameworks/processes at all levels should be the active engagement and concern of the citizenry.